New Prothrombin Mutation (Arg596Trp, Prothrombin Padua 2) Associated With Venous Thromboembolism. Issue 5 (May 2016) - Bulato, Cristiana; Radu, Claudia Maria; Campello, Elena; Gavasso, Sabrina; Spiezia, Luca; Tormene, Daniela; Simioni, Paolo
Abstract : Objective—: Two different prothrombin variants, p.Arg596Leu and p.Arg596Gln, conferring antithrombin resistance to patients with venous thromboembolism have been recently reported. Here, we describe a novel substitution affecting Arg596 of prothrombin molecule (Arginine596 to Tryptophan or p.Arg596Trp or Arg221aTrp in the chymotrypsinogen numbering system or prothrombin Padua 2) in 2 Italian families with venous thromboembolism. Approach and Results—: Prothrombin Padua 2 has been characterized either in plasma of carriers or using Arg596Trp recombinant prothrombin. Routine coagulation tests, thrombin generation, and antithrombin resistance tests were performed, as well as measurement of the levels of thrombin–antithrombin complexes. All carriers were heterozygotes and presented with a mild reduction of the prothrombin activity. Thrombin generation in carriers showed only a markedly prolonged decay. This finding was confirmed in plasma reconstituted with Arg596Trp recombinant prothrombin mimicking a homozygous condition, which showed longer decay and higher endogenous thrombin potential in thrombin generation than wild-type recombinant prothrombin reconstituted plasma. Patient's plasma as well as Arg596Trp recombinant prothrombin showed a clear thrombin resistance to antithrombin inactivation. These findings were supported by the assessment of thrombin–antithrombin complexes formation, which was strongly reduced for Arg596Trp recombinant prothrombin as compared with wild-type recombinant prothrombin. In a series of 400 unrelated consecutive patients with venous thromboembolism, 2 carriers of prothrombin Padua 2 were found (estimated prevalence of 0.5%). Conclusions—: Our study showed that prothrombin Padua 2 induces antithrombin resistance and is associated with an increased risk of venous thromboembolism. Codon 596 (CGG) of prothrombin is a hot spot for mutations, which constitute a new and relatively frequent cause of inherited thrombophilia. Abstract : Supplemental Digital Content is available in the text.